453 Intra-tumoural electro-chemotherapy (ECT) with bleomycin for palliation of cutaneous recurrence in gynaecological malignancy. (4th December 2020) - Rundle, Stuart; Ang, Christine; Fasih, Tani; Korompelis, Porfyrios; Ratnavelu, Nithya
Abstract : Introduction/Background: ECT utilises pulsed electrical current to transiently increase cell membrane permeability to the cytotoxic agent, bleomycin. We present the use of ECT in patients with recurrent gynaecological malignancy previously treated with a combination of surgery or radiotherapy, experiencing symptoms from cutaneous lesions. This report presents evidence of the role for ECT in second and third line treatment. Methodology: Between July 2017 and August 2019, 6 patients with cutaneous recurrence of gynaecological malignancy (5 vulvar SCC and 1 high grade serous ovarian cancer) were treated with intra-tumoural bleomycin (9000 iu or 15000 iu, dependent on tumour volume) and pulsed-probe electroporation. Response was assessed clinically in routine follow up or following self-referral with return of symptoms. Post procedure pain scores were collated as part the quality of life evaluation. Results: Median treated tumour diameter was 6 cm (range 2 – 12 cm). Pain scores peaked between day 2 and day 7 post-procedure. The median progression free interval was 3.6 months (range 0.8 – 6.7 months). Following ECT treatment 2 patients continued to receive supportive care. Two patients underwent repeat treatment with ECT and reported symptom improvement with each treatment. Due to further progression two patients underwent radical surgery and one patient received palliative chemotherapy. Conclusion: ECT should be considered for patients with symptomatic cutaneous recurrence of gynaecological malignancy who have previously had multi-modal treatment. It can achieve symptom control and reduce the need for radical surgery in this palliative setting. Disclosures: The Authors have no conflicts of interest to disclose.